2019
DOI: 10.1175/jpo-d-18-0213.1
|View full text |Cite
|
Sign up to set email alerts
|

The Loop Current: Observations of Deep Eddies and Topographic Waves

Abstract: A set of float trajectories, deployed at 1500- and 2500-m depths throughout the deep Gulf of Mexico from 2011 to 2015, are analyzed for mesoscale processes under the Loop Current (LC). In the eastern basin, December 2012–June 2014 had >40 floats per month, which was of sufficient density to allow capturing detailed flow patterns of deep eddies and topographic Rossby waves (TRWs), while two LC eddies formed and separated. A northward advance of the LC front compresses the lower water column and generates an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…However, the coupling mechanisms are more complicated than merely involving baroclinic instability and TRW propagation. For example, potential vorticity anomalies in the deep ocean induced by the upper-ocean perturbations can contribute to the coupling process as well (e.g., Donohue et al, 2008;Hamilton, 2009;Hamilton et al, 2019;Tenreiro et al, 2018), which is not analyzed in this study. Baroclinic Kelvin waves are Figure 17.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the coupling mechanisms are more complicated than merely involving baroclinic instability and TRW propagation. For example, potential vorticity anomalies in the deep ocean induced by the upper-ocean perturbations can contribute to the coupling process as well (e.g., Donohue et al, 2008;Hamilton, 2009;Hamilton et al, 2019;Tenreiro et al, 2018), which is not analyzed in this study. Baroclinic Kelvin waves are Figure 17.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is implied that this mechanism is responsible for the coupling in the western GoM (Tenreiro et al, 2018). Moreover, other observational as well as numerical studies highlight the importance of both barotropic and baroclinic instability of the LC, the LCEs, and the LC front eddies (LCFEs) in the generation of lower‐layer cyclones and anticyclones (Chérubin et al, 2006; Donohue et al, 2016; Hamilton, Bower, et al, 2016; Hamilton et al, 2019; Hamilton, Lugo‐Fernández, et al, 2016; Hurlburt & Thompson, 1980; Oey, 1996, 2008; Xu et al, 2013). Atmospheric forcing (Welsh & Inoue, 2000) and topography are important factors in influencing the dynamics in the deep ocean as well (Cardona & Bracco, 2016; Donohue et al, 2008; Frolov et al, 2004; LaCasce, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Until recent decades, this concept was nullified by multiple deep-ocean observations, revealing considerable motions thousands of meters below the global ocean surface. For example, in the North Atlantic, low-frequency variability in the deep current with periods of several days to hundreds of days has been revealed (Thompson and Luyten 1976;Hogg 1981;Hamilton 1990;Pickart and Watts 1990;Peña-Molino et al 2012;Hamilton et al 2019); the deep western boundary current in the Southern Pacific is modulated by variability with a period of 10-50 days (Whitworth III et al 1999); and in the Indian Ocean's Mascarene Basin, deep water has large velocity fluctuations of 40-60 days (Quadfasel and Swallow 1986;Schär and Davies 1988;Warren et al 2002). In addition, a recent study in the South China Sea (SCS) reported that the temporal variability in the deep western boundary current is dominated by intraseasonal fluctuations by a period of approximately 90 days and that the amplitude of the deep western boundary current variability exceeds its mean value (Zhou et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The other cyclones either do not experience a change in their KE or the change is presumably due to other processes such as vortex merging and splitting when KE and SSH variability are not correlated. The decay in KE of the LCFEs is presumably related to the conversion of energy into other motions such as topographic Rossby waves (LaCasce, ; Hamilton, ; Hamilton et al, ) and to dissipation through friction. The mechanism of LCFE intensification will be discussed in sections and .…”
Section: Resultsmentioning
confidence: 99%